Dopaminergic Control of Inflammation and Glycemia in Sepsis and Diabetes - Feketeova, Eleonora; Li, Zhifeng; Joseph, Biju; Shah, Roshan; Spolarics, Zoltan; Ulloa, Luis (Frontiers in Immunology, 2018)
Most preclinical treatments for sepsis failed in clinical trials in part because the experimental models of sepsis were performed on healthy animals that do not mimic septic patients. Here, we report that experimental diabetes worsens glycemia, inflammation and mortality in experimental sepsis. Diabetes increases hyperglycemia, systemic inflammation and mortality in sepsis. Diabetes exacerbates serum TNF levels in sepsis by increasing splenic TNF production. Both serum from diabetic mice and glucose increase cytokine production in splenocytes. Anti-inflammatory treatments can’t control hyperglycemia and are less effective in diabetic patients. By contrast, dopaminergic agonist type-1, fenoldopam, attenuates hyperglycemia and systemic inflammation in diabetic septic mice by inhibiting splenic p65NF-kB phosphorylation. Fenoldopam inhibits TNF production in splenocytes even at high glucose concentrations and inhibits the canonical NF-kB pathway by inhibiting p65RelA and p50NF-kB1 phosphorylation without affecting the non-canonical NF-kB proteins. Treatment with fenoldopam ‘rescues’ diabetic mice from established polymicrobial peritonitis even when the treatment is started after the onset of sepsis. These results suggest that dopaminergic agonists can control hyperglycemia, systemic inflammation and provide therapeutic advantages for treating diabetic patients with sepsis in a clinically relevant time frame.